2020
DOI: 10.1111/acel.13204
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 sustains female fertility by slowing age‐related decline in oocyte quality required for post‐fertilization embryo development

Abstract: Mammalian oocytes are heavily reliant on mitochondrial oxidative phosphorylation (OXPHOS) for ATP generation using pyruvate derived from surrounding cumulus cells (Eppig, 1976; Johnson, Freeman, Gardner, & Hunt, 2007). Notably, mitochondria produce the vast majority of cellular free radicals and reactive oxygen species (ROS), which arise as a by-product of OXPHOS (Figueira et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…40,46 In line with this, we showed that deletion from oocytes of the sirtuin, SIRT1 (a major regulator of mitochondrial function), results in increased oxidative stress that compromises embryonic development leading to early-onset infertility in female mice. 47 There is therefore intense interest in the use of antioxidants for improving oocyte quality. One example is coenzyme Q10 (CoQ10), a well-known component of the mitochondrial electron transport chain.…”
Section: Prospects and Challenges For Diagnosing And Improving Poor Omentioning
confidence: 99%
“…40,46 In line with this, we showed that deletion from oocytes of the sirtuin, SIRT1 (a major regulator of mitochondrial function), results in increased oxidative stress that compromises embryonic development leading to early-onset infertility in female mice. 47 There is therefore intense interest in the use of antioxidants for improving oocyte quality. One example is coenzyme Q10 (CoQ10), a well-known component of the mitochondrial electron transport chain.…”
Section: Prospects and Challenges For Diagnosing And Improving Poor Omentioning
confidence: 99%
“…However, Iljas et al found that SIRT1‐knockout mice do not exhibit any such impact on the oocytes, rather it affects the early cleavage divisions post‐fertilisation secondary to OS within the embryo. Furthermore, they demonstrated that despite lack of mitochondria in the aged SIRT1‐deficient oocytes, the cause of infertility is the same; post‐fertilisation embryo cleavage defect 41 . This suggest that in aged oocyte the reduced maternal SIRT1 becomes critical for the embryonic development as the OS developed during this phase lacks the compensatory mechanism offered by SIRT1 (in young oocytes).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that SIRT1 plays a role in oocyte function in older ages (Iljas et al, 2020) embryogenesis. Antral follicles differ substantially from primordial follicles, as is evident from the wave-like pattern of DNA methylation.…”
Section: Discussionmentioning
confidence: 99%